ӘМЕТ ШАМУРАТОВТЫҢ ПРОЗАСЫНДА ОБРАЗЛАР ТИПОЛОГИЯСЫ - Бекбергенова, М.Д. (SCIENCE and SOCIETY, 2017)
The article deals with the issues of typology of characters in the works of the Karakalpak writer Amet Shamuratov, national literary traditions, successive relation of folkloric characters with artistic characters of modern prose. The author of the article also studies the artistic fiction and creative deflection through the writer's prism.
Keywords: writer; creative individuality; artistic fiction; plot; image; theme; problem; typology